Plant Spacing Variations on Cell Number and Agar Content in Gracilaria verrucosa - Purwanti, Andi; Mulyani, Sri; Budi, Sutia (Universitas Diponegoro, 2024)
The primary issue at the Gracilaria verrucosa seaweed cultivator is the low productivity associated with current cultivation methods. Analyzing cell number and agar content provides valuable insights into seaweed cultivation productivity, growth activity, nutrient absorption, and chemical composition. This research aims to examine how variations in planting distance affect the cell number and agar content of Gracilaria verrucosa. The research was conducted at the Maranak Experimental Pond Installation, Brackish Water Aquaculture Fisheries Research Institute, located in Marannu Village, Lau District, Maros Regency. Analysis of cell numbers and agar content was performed at the Fisheries Research Institute Laboratory of the Brackish Water Aquaculture Center from June to July 2024. Utilizing a completely randomized quantitative experimental design with four treatments and three repetitions, the research included: Treatment A (planting distance 20 cm), Treatment B (30 cm), Treatment C (40 cm), and Treatment D (50 cm). The results indicated that planting distance significantly impacts cell number, with the 50 cm distance yielding the highest average cell count of 213.00 ± 9.64. Similarly, planting distance affects agar content, with the 50 cm distance producing the highest agar content of 27.31%. Therefore, a planting distance of 50 cm is identified as the most effective, resulting in both the highest number of cells and agar content.